Diffusive dynamics of nanoparticles in ultra-confined media. Issue 38 (17th August 2015) - Jacob, Jack Deodato C.; He, Kai; Retterer, Scott T.; Krishnamoorti, Ramanan; Conrad, Jacinta C.
Abstract : Hydrodynamic models incorporating volume exclusion and hydrodynamic drag describe the slowing of diffusion of nanoparticles strongly confined in nanopost arrays. Abstract : Differential dynamic microscopy (DDM) was used to investigate the diffusive dynamics of nanoparticles of diameter 200–400 nm that were strongly confined in a periodic square array of cylindrical nanoposts. The minimum distance between posts was 1.3–5 times the diameter of the nanoparticles. The image structure functions obtained from the DDM analysis were isotropic and could be fit by a stretched exponential function. The relaxation time scaled diffusively across the range of wave vectors studied, and the corresponding scalar diffusivities decreased monotonically with increased confinement. The decrease in diffusivity could be described by models for hindered diffusion that accounted for steric restrictions and hydrodynamic interactions. The stretching exponent decreased linearly as the nanoparticles were increasingly confined by the posts. Together, these results are consistent with a picture in which strongly confined nanoparticles experience a heterogeneous spatial environment arising from hydrodynamics and volume exclusion on time scales comparable to cage escape, leading to multiple relaxation processes and Fickian but non-Gaussian diffusive dynamics.